2013
DOI: 10.4102/phcfm.v5i1.480
|View full text |Cite
|
Sign up to set email alerts
|

Availability of tuberculosis infection control plans at rural hospitals of Vhembe district, Limpopo Province of South Africa

Abstract: BackgroundIn Limpopo province the rate of new tuberculosis (TB) cases increase daily. The Infection Control (IC) plan is one of the essential actions for TB IC. This study aimed to establish the availability of these plans at health care facilities.ObjectivesThe objectives were to explore and describe the awareness and knowledge of health care workers (HCWs) of the availability and content of TB IC plan; and to identity the role of infection control committees from the perspective of HCWs.MethodA qualitative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 7 publications
3
10
0
Order By: Relevance
“…Nurses and patients were at a great risk of contracting TB infection in the wards. The findings of this study agree with those study by Tshitangano et al [8], which concluded that infection control plans are not available at the hospitals in Vhembe District, and this results in a high risk of TB infection transmission in the hospitals.…”
Section: Good Infection Control and Prevention Measuressupporting
confidence: 92%
See 2 more Smart Citations
“…Nurses and patients were at a great risk of contracting TB infection in the wards. The findings of this study agree with those study by Tshitangano et al [8], which concluded that infection control plans are not available at the hospitals in Vhembe District, and this results in a high risk of TB infection transmission in the hospitals.…”
Section: Good Infection Control and Prevention Measuressupporting
confidence: 92%
“…In 2012, Vhembe district had the highest number of TB patients in the Limpopo Province [7]. Tshitangano et al [8], further indicated that TB infection control plans were not available at hospitals in Vhembe district and this contributed to the high number of TB patients. Infection control requires both human and material resources for maintenance and support [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, Vhembe district was also reported to have the highest number of TB patients in the Limpopo Province [7]. Tshitangano, Maputle and Netshikweta (2013) [8] point out that TB infection control plans are not available at hospitals in Vhembe district and this contributes to the high number of TB patients. Infection control requires both human and material resources.…”
Section: Introductionmentioning
confidence: 99%
“…After considering the variety of constructs for use, Lincoln and Guba's (1985) criteria for trustworthiness was determined to be the most appropriate for the current study. Also supporting the researcher's decision to use trustworthiness was the number of researchers who had used trustworthiness as their criteria for rigor in phenomenological research conducted in South Africa (Brysiewicz, 2008;Collier-Reed, Ingerman, & Berglund, 2009;Hoffman, Myburgh, & Poggenpoel, 2010;Mavundla, 2000;Pietersen, 2007;Tshitangano, Maputle, & Netshikweta, 2013;Warden, Mayers, & Kathard, 2008). Lincoln and Guba's (1985) criteria for trustworthiness includes credibility, transferability, dependability, and conformability.…”
Section: Trustworthinessmentioning
confidence: 99%